Mutu Pelayanan Kesehatan Pasien Rawat Inap oleh Tenaga Kesehatan di Pusksesmas Sonimanu Kabupaten Rote Ndao - Helmi M. Bolla; Yoseph Kenjam; Tadeus A. L. Regaletha (Lontar : Journal of Community Health, 2019)
Service Quality can be obtained if what is expected by the patient to the service provider is in accordance with the patient's requirements. This study aims to determine the quality of patient health services by health workers at the Sonimanu health center in 2019. The sample in this study was all In patients with a total sample of 73 people the sampling technique in this study was totally sampling. Data collection was carried out with 20 items of hope and reality questionnaire, which is a quantitative description of this type of study. The analysis conducted is univariate using Importance Performance Analysis. The results of this study indicate that the value of conformity between expectations and quality of inpatient services of health workers to the tangible dimension is 97.28% (Very Satisfied), reliably 95.27% (Very Satisfied), responsiveness 86.38% (Satisfied), assurance 98.14% (Very Satisfied), empathy 97.21% (Very Satisfied). There is one attribute of inadequate quality of service that is a good nutrition officer providing and helping patients with dietary needs (58.42%), it is expected that the health staff at the Sonimanu health center need to prioritize and be more responsive in paying attention to the rights or needs of Inpatients. It is recommended that the quality of inpatient health services by health workers need to be further improved, especially in the dimension of responsiveness.